PENGARUH INPUT PRODUKSI TERHADAP KUALITAS BIJI KAKAO DAN PENDAPATAN USAHATANI KAKAO DI DESA SEJAHTERA KECAMATAN PALOLO KABUPATEN SIGI - Nurhidaya Nurhidaya; Made Antara; Effendy Effendy (Universitas Tadulako, 2015)
This research aimedto: (1) analyze the influence of inputs on the quality of cocoa beans at Sejahtera VillagePalolo Sub District Sigi District and (2) analyze cacao farm income at Sejahtera VillagePalolo Sub District Sigi District. The method usedwas asurvey and samples were taken using a simple random technique. The number of samplesused asrespondentswas 52household head. The results showed that (1) F test = 65.429 with probability p = 0.000 <0.05 at α = 5% indicates the rejection of the null hypothesis suggesting thatsuch independent variables as urea fertilizer (X1), KCl fertilizer (X2), SP36 fertilizer (X3), pesticides (X4), and labor (X5) have simultaneously significant effect on the number of seeds per 100 g of dry cocoa beans at Sejahtera Village Palolo Sub District. Partially, urea fertilizer (X1), KCl fertilizer (X2), SP36 fertilizer (X3), pesticides (X4), and labor (X5) significantly affects the number of seeds per 100 g of dry cocoa beans at the level of 95% and (2) the average total cost of the cacaa farming is IDR 14,103,106.34/1.61 ha/year equal to IDR 8,759,693.38/ha/year. The average cocoa farm revenueisIDR 40,060,300.00/1.61 ha/year. Withthe average selling price of IDR 35,000.00 /kg, the average cocoa farming revenue isIDR 25.957.193,66/1.61 ha/year equal to IDR 16,122,480.53/ha/year. The income of cocoa farming in the Sejahtera village per month is IDR 1,343,540/ha.Keywords :Cacao farm, income, input production, andquality of cocoa beans.